Forest loss and landscape pattern change cause watersheds to release more young water - Ming Qiu; Xiaohua Wei; Yiping Hou (Proceedings of the National Academy of Sciences, 2026)
The hydrological functions of forests are well recognized, but their influence on water storage and release dynamics remains poorly quantified. The fraction of young water ( F yw )—the proportion of streamflow younger than 2 to 3 mo—serves as an integrative indicator of a watershed’s capacity to retain and release precipitation. Here, by analyzing F yw across 657 watersheds worldwide, we found that forest cover exhibited a significant negative relationship with F yw . The causality was further corroborated through a meta-analysis of postdeforestation F yw trends, confirming that forest loss accelerates the conversion of recent precipitation into streamflow. This effect was most pronounced in watersheds with shallow groundwater, highlighting the role of forests in regulating rapid, near-surface flowpaths. Beyond total forest cover, we found that forest landscape patterns also exerted influences: A lower proportion of forest edge was associated with higher F yw , but only in sparsely forested watersheds ( ≤ ∼ 40% forest cover), where the edge-enhanced evapotranspiration was most pronounced. This global synthesis not only reinforces the hydrological value of forest conservation and restoration but also highlights that deliberate planning of forest landscape patterns can help mitigate the hydrological consequences of forest loss. Together, these findings demonstrate that integrating forest protection with forest landscape planning is essential for sustaining hydrological functions.